MycoNews 2022: editorial, news, reports, awards, personalia, and book news - David L. Hawksworth (IMA Fungus)
Abstract This fourth annual edition of MycoNews starts with an editorial asking if mycology is approaching a tipping point, and note of the journal’s 2021 Impact Factor almost doubling from 2020. Updated information and new speakers for IMC12 in 2024 is presented. Reports are provided for the Rise of the Fungi symposium in Amsterdam and of MycoRiseUP! in Warsaw in 2022. Information on activities of the International Commission on the Taxonomy of Fungi (ICTF) in the last two years are presented, including the formation of new Working Groups. Procedures for the nomination of IMA awards and for nomenclature proposals to be presented at IMC12 are provided. The Westerdijk Institute awards to Feng-Yan Bai and Marc Stadler are recorded, and Michael Wingfield and Geoffrey Kibby are congratulated on special awards they have received. Tributes are paid to the passing of two distinguished mycologists during the year, John Parmelee and John Pitt. Reviews of six mycological books published in 2021–22 are also provided.